Integrated chip-size antenna for wireless microsystems : fabrication and design considerations - Mendes, P. M. (2003)
This paper reports on fabrication and design considerations of an integrated folded shortedpatch chip-size antenna for applications in short-range wireless microsystems and operating frequency of 5.7 GHz. Antenna fabrication is based on wafer-level chip-scale packaging (WLCSP) techniques and consists of two adhesively bonded glass wafers with patterned metallization and through-wafer electrical interconnects. Two different fabrication options based on via formation in glass substrates using excimer laser ablation or powder blasting are presented.